THE EFFECT OF ORGANIC AND INORGANIC FERTILIZER DOSES ON THE GROWTH AND DEVELOPMENT OF RED CHILI PLANTS (Capsicum annuum L.) - Tarigan, Rio Stepanus (Jurnal Teknologi dan Ilmu Pertanian, 2025)
This study aimed to determine the effect of organic and inorganic fertilizer dosages on the growth and development of red chili plants (Capsicum annuum L.). The experiment was conducted using a factorial Randomized Block Design (RBD) with 9 treatment combinations (3 × 3). The first factor was chicken manure with the following doses: P0 = control, P1 = 2.6 kg, and P2 = 5.2 kg. The second factor was NPK 16:16:16 fertilizer with the following doses: N0 = control, N1 = 100 g, and N2 = 200 g. The experimental procedures included land preparation, mulching, planting, watering, replanting, weeding, and harvesting. The observed parameters were plant height (cm), stem diameter, yield per plot, and descriptions of pests and diseases (OPT) attacking the chili plants. Application of chicken manure did not significantly affect the observed parameters, although it showed an increase in plant height, stem diameter, and yield per plot compared to the control. The application of chicken manure and NPK fertilizer at 2, 4, 6, and 8 weeks after planting (WAP) had no significant effect on chili plant height. However, plants treated with chicken manure and NPK tended to grow taller than those without fertilization. Similarly, the combined application of chicken manure and NPK had no significant effect on stem diameter at 2, 4, 6, and 8 WAP. In contrast, the application of chicken manure and NPK significantly affected fruit weight per plot. The highest fruit weight was obtained in the N2 treatment, which was significantly different from N0 and N1. The interaction between chicken manure and NPK fertilizer had no significant effect on any of the observed parameters.